Remote patient monitoring for chronic heart failure in France: When an innovative funding program (ETAPES) meets an innovative solution (Satelia® Cardio). (August 2022) - Pages, N; Picard, F; Barritault, F; Amara, W; Lafitte, S; Maribas, P; Abassade, P; Labarre, J Ph; Boulestreau, R; Chaouky, H; Abdennadher, M; Lemieux, H; et al.
Introduction: Remote patient monitoring (RPM) is a telehealth activity to collect and analyze patient health or medical data. Its use has expanded in the past decade and has improved medical outcomes and care management of non-communicable chronic diseases. However, implementation of RPM into routine clinical activities has been limited. The objective of this study was to describe the French funding program for RPM (known as ETAPES) and one of the RPM solution providers (Satelia®) dedicated to chronic heart failure (CHF). Methods: A descriptive assessment of both the ETAPES funding program and Satelia® RPM solution was conducted. Data were collected from official legal documents and information that was publicly available online from the French Ministry of Health. Results and Discussion: ETAPES was formally created in 2016 based on previous legislation pertaining to the national health insurance funding strategy. However, it only started to operate in 2018. Patients with CHF were only eligible if they were at medium or high risk of re-hospitalization with a New York Heart Association (NYHA) score superior or equal to two and a BNP>100 pg/ml or NT pro BNP>1000 pg/ml. Medical monitoring was supported through the therapeutic education of a patient on the RPM model of care with a minimum of three training sessions during the first six months. The use of Satelia® Cardio is noteworthy since it relies only on symptomatic monitoring through which the patient manually reports their information by answering a simple questionnaire on a regular basis and does not rely on any connected devices. Conclusion: Innovative funding programs and solutions for RPM need real-world evaluation in the future.